Penerapan Model Pembelajaran Problem Based Learning (PBL) dengan Pendekatan Teaching at the Right Level (TaRL) dalam Meningkatkan Hasil Belajar kognitif Siswa kelas X pada Materi Inovasi Teknologi Biologi SMA - Cholil As’ad, Muhammad; Sulistyarsi, Ani; Sukirmawati, Juli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to increase student activity and learning outcomes in Biology learning through the Problem Based Learning model with a Teaching at the Right Level (TaRL) Approach in class X E SMAN 6 Madiun in the even semester of the 2022/2023 school year. Methods of data collection using Observation, Cognitive Tests, Learning Outcomes Documents. Having final performance indicators 83% (30 out of 36 students) who get the complete category, with details of pre-cycle learning outcomes get 22% (8 out of 36 students) get the complete category, cycle I assessment of learning outcomes get 58% (21 out of 36 students ) get the complete category, the second cycle of assessment of learning outcomes get 83% (30 of 36 students) get the complete category. Learning outcomes have met the KKM score and achieved performance indicators of success ≥ 83%. It can be concluded from this study that the application of the Problem Based Learning model with the Teaching at the Right Level (TaRL) approach can improve student learning activities and student biology learning outcomes. Keywords: Learning Activities, Cognitive Learning Outcomes, PBL Models, TaRL